Clinical features which predict neuronal surface autoantibodies in new-onset focal epilepsy: implications for immunotherapies - McGinty, R; Handel, A; Moloney, T; Ramesh, A; Fower, A; Torzillo, E; Kramer, H; Howell, S; Waters, P; Adcock, J; Sen, A; Lang, B; et al. (BMJ Publishing Group, 2020)
Objective To generate a score which clinically identifies surface-directed autoantibodies in adults with new-onset focal epilepsy, and evaluate the value of immunotherapy in this clinical setting.